Fasilitas Kredit Usaha Rakyat (KUR) Dalam Meningkatkan Usaha Kecil Mikro Kecil dan Menengah (UMKM) di Desa Binuang Kecamatan Libureng: People's Business Credit Facility (KUR) in Improving Small, Micro, Small and Medium Enterprises (MSMEs) in Binuang Village, Libureng District - Reski Rahayu Fitri; Chalid Imran Musa; Uhud Darmawan Natsir (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2023)
The type of research used in this research is qualitative research. Data collection was carried out using interviews, observation and documentation methods. The results of the research show that the influence of efforts to involve People's Business Credit (KUR) in efforts to increase MSMEs in Binuang Village, Libureng District has had a very positive impact, MSME owners are greatly helped in developing their businesses, by increasing income. the goods they sell, because with KUR, MSME owners obtain additional capital. There has been a very significant increase; Turnover, monthly profit, working hours and number of workers are caused by capital assistance.